Corrigendum - Agrivita Agrivita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Corrigendum to “Synergistic Action of PGPR and Biofungicide with Active Ingredient of Cladosporium clasporioides to Control White Rust on Chrysanthemum” [AGRIVITA Journal of Agricultural Science, 44(1), 31-39]